2018
DOI: 10.1002/admi.201701666
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Electrocatalysis on Pd‐Ni Core–Shell Nanoparticles for Hydrogen Oxidation Reaction in Alkaline Medium

Abstract: 1 and − − 1.38 mA cm Pd 2 at 0.1 V versus reversible hydrogen electrode at 298 K. These are the highest values reported so far for an NiPd catalyst. By design, the synthetic approach is generic and can be applied to any pair of metals, either PGM or other transition metals, to synthesize alloyed or core-shell electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 36 publications
(41 reference statements)
1
29
0
Order By: Relevance
“…139,142 In addition, it was proposed that the activation energy for both water formation and water dissociation decrease at the interface between Ni3N and Ni 139,142 . As a result, the reported carbon-supported Ni3N [155][156][157] or by tuning the hydrogen binding energy. 134 Considering the above-mentioned reasons, in what follows, we will only discuss NiM systems with a non-precious second component (Table 1).…”
Section: Hor On Monometallic Ni Electrodesmentioning
confidence: 92%
“…139,142 In addition, it was proposed that the activation energy for both water formation and water dissociation decrease at the interface between Ni3N and Ni 139,142 . As a result, the reported carbon-supported Ni3N [155][156][157] or by tuning the hydrogen binding energy. 134 Considering the above-mentioned reasons, in what follows, we will only discuss NiM systems with a non-precious second component (Table 1).…”
Section: Hor On Monometallic Ni Electrodesmentioning
confidence: 92%
“…[ 3 ] However, the kinetics of alkaline hydrogen oxidation reaction (HOR) is normally two orders of magnitude lower than that in acidic media, [ 4 ] and thus requiring a large quantity of noble metal electrocatalysts to accelerate the reaction. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] Many recent studies have supported this bifunctional mechanism. [ 49–53 ] Besides, Wei and co‐workers studied the role of OH* in the HOR on Pt(110), Ir(110), Pd(110), Ni(110), and PtRu(110) using density functional theory (DFT) calculations. [ 54 ] The authors found that OH* adsorption induces remarkably different effects on H* and adsorbed water molecule (H 2 O*), and the combination of Δ G OH* , Δ G H* , and Δ G H2O* should be evaluated altogether to achieve a more precise and comprehensive understanding on the HOR/HER mechanism.…”
Section: Hor Mechanismmentioning
confidence: 99%